Gamilaraay, Yuwaalaraay & Yuwaalayaay dictionary - Lissarrague, Amanda, 1958-; Ash, Anna.; Giacon, John. (Alice Springs, N.T. : IAD Press, 2003)
The central north of New South Wales is the home of the Gamilaraay, Yuwaalaraay and Yuwaalayaay people, one of the largest Aboriginal language groups in the state. For many years their languages were in decline, but in recent years they have been revived by a growing number of people in the area. This book is a result of their efforts. It contains the most extensive list of Gamilaraay, Yuwaalaraay and Yuwaalayaay words yet published; detailed information about words, and example sentences to illustrate their uses; comprehensive word lists to locate words by their English equivalent; and a learner's guide to the grammar of the languages.
Includes G/Y/Y to English dictionary, English to G/Y/Y word lists, Learner's guide.
Bibliography: p. 14-15.
Keywords: Kamilaroi language -- Dictionaries -- English; English language -- Dictionaries -- Gamilaraay; Yuwaalaraay language -- Dictionaries -- English; English language -- Dictionaries -- Yuwaalaraay; Gamilaraay / Gamilaroi / Kamilaroi language (D23) (NSW SH55-12); Language - Vocabulary - Plant names; Language - Vocabulary - Word lists; Yuwaalaraay / Euahlayi / Yuwaaliyaay language (D27) (NSW SH55-07); Language - Vocabulary - Dictionaries and glossaries; Social organisation - Kinship - Kinship terms; Language - Maintenance; Language - Vocabulary - Place names; Language - Vocabulary - Animal names; Gamilaraay / Gamilaroi / Kamilaroi language D23.; Northern New South Wales (N NSW SH55, SH56)